The American Spirit : Who We Are and What We Stand For - David McCullough (Simon ?&Schuster Paperbacks, 2017)
A timely collection of speeches by David McCullough, the most honored historian in the United States—winner of two Pulitzer Prizes, two National Book Awards, and the Presidential Medal of Freedom, among many others—that reminds us of fundamental American principles.